Medical follow-up of workers exposed to lung carcinogens: French evidence-based and pragmatic recommendations - Fleur Delva; Jacques Margery; François Laurent; Karine Petitprez; Jean-Claude Pairon; RecoCancerProf Working Group (BMC, 2017)
Abstract Background The aim of this work was to establish recommendations for the medical follow-up of workers currently or previously exposed to lung carcinogens. Methods A critical synthesis of the literature was conducted. Occupational lung carcinogenic substances were listed and classified according to their level of lung cancer risk. A targeted screening protocol was defined. Results A clinical trial, National Lung Screnning Trial (NLST), showed the efficacy of chest CAT scan (CT) screening for populations of smokers aged 55-74 years with over 30 pack-years of exposure who had stopped smoking for less than 15 years. To propose screening in accordance with NLST criteria, and to account for occupational risk factors, screening among smokers and former smokers needs to consider the types of occupational exposure for which the risk level is at least equivalent to the risk of the subjects included in the NLST. The working group proposes an algorithm that estimates the relative risk of each occupational lung carcinogen, taking into account exposure to tobacco, based on available data from the literature. Conclusion Given the lack of data on bronchopulmonary cancer (BPC) screening in occupationally exposed workers, the working group proposed implementing a screening experiment for bronchopulmonary cancer in subjects occupationally exposed or having been occupationally exposed to lung carcinogens who are confirmed as having high risk factors for BPC. A specific algorithm is proposed to determine the level of risk of BPC, taking into account the different occupational lung carcinogens and tobacco smoking at the individual level.